2020
DOI: 10.1101/2020.06.11.20126359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemoprophylaxis of COVID-19 with hydroxychloroquine - a study of health care workers attitude, adherence to regime and side effects

Abstract: Background: There are apprehensions amongst healthcare worker (HCWs) about COVID-19. The HCWs have been given hydroxychloroquine (HCQ) chemoprophylaxis for seven weeks as per Government of India guidelines. Objectives: To assess the apprehensions amongst HCWs about COVID-19 and to document accessibility, adherence and side effects related to HCQ prophylaxis in HCWs. Methods: A longitudinal follow up study was conducted in a tertiary care hospital. HCQ was given in the dose of 400 mg twice on day one, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This finding was similar to the one reported by Bhattacharyya et al, who reported that the HCQ prophylaxis was accepted by 76% of the HCWs. Since our study included primarily doctors who were aware of the limited evidence of the effectiveness of HCQ prophylaxis against COVID-19, perhaps relatively lesser acceptance was observed [12]. About 70% of the participants knew the correct dose, duration, and contraindications associated with HCQ, but a screening test (ECG) was done only in half of the participants initiating HCQ prophylaxis.…”
Section: Table 1 Results Of Questions Related To Awareness Of Hcq Pro...mentioning
confidence: 99%
“…This finding was similar to the one reported by Bhattacharyya et al, who reported that the HCQ prophylaxis was accepted by 76% of the HCWs. Since our study included primarily doctors who were aware of the limited evidence of the effectiveness of HCQ prophylaxis against COVID-19, perhaps relatively lesser acceptance was observed [12]. About 70% of the participants knew the correct dose, duration, and contraindications associated with HCQ, but a screening test (ECG) was done only in half of the participants initiating HCQ prophylaxis.…”
Section: Table 1 Results Of Questions Related To Awareness Of Hcq Pro...mentioning
confidence: 99%
“…In a Delhi-based study, the authors found that doctors showed least acceptance of HCQ chemoprophylaxis. [17] The test of association performed between "compliance with the recommendation" and "gender" (χ 2 P = 0.68), "geographical region" (χ 2 P = 0.21), "practice setting" (χ 2 P = 0.24), and "specialty" (χ 2 P = 0.78) yielded non- Forty-three percent (n = 15) of respondents who work in the ICU stated that they took the chemoprophylaxis as per ICMRs recommendation. However, this percentage declined to 37 (n = 7) in outpatient clinics, 30 (n = 6) among respondents who work in emergency rooms, and 28 (n = 5) in inpatient wards.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Bhattacharya et al (2020) reported that one in five health care workers who complied with the HCQ chemoprophylaxis developed mild side effects. [17] Dhamija et al reported that 36% of the respondents in their global survey reported side effects due to HCQ/chloroquine prophylaxis. [20] On the contrary, one study found no QT prolongation in health care workers who complied with the ICMRs chemoprophylaxis recommendation.…”
Section: Concerns About Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permission has been given by the FDA for the use of HCQ in severe COVID-19 cases. There are contradictory reports on the effectiveness of HCQ in COVID-19 therapy, and relatively few evidence on the safety and efficacy of COVID-19 chemoprophylaxis are available in the published literature [14][15][16].…”
Section: Discussionmentioning
confidence: 99%